The Benefits and Pitfalls of Public Private Partnerships: Case Study of the Suez Canal Container Terminal, Egypt - Elswesy, Magda (AUC Knowledge Fountain, 2025)
The study explores the public-private partnerships (PPPs) in constructing, managing, and operating container terminals in Egypt. It examines the benefits the public sector gains from such collaborations and the pitfalls that can be mitigated to foster more effective institutional cooperation. The study specifically focuses on enhancing Egypt's marine container terminals through these partnerships, emphasizing the potential use of growing technology to enable equipment automation. It also highlights concerns regarding the risk of mismanagement of Egyptian terminals, arising from insufficient expected volume to ensure appropriate profitability, especially with the opening of new terminals. The study adopts a qualitative methodology and presents a case study of the Suez Canal Container Terminal, a joint venture in one of Egypt's most strategic locations. It utilizes the input of 13 semi-structured in-depth interviews with field experts who maintain widespread knowledge of the industry. The study's key findings reveal the benefits and pitfalls of PPP in Egyptian Maritime Container Terminals. Among the benefits accruing to the public sector are the revenue income from the lease, the use of experts' experience and finances, the employment opportunities, and the community projects. Meanwhile, some of the pitfalls identified include missing some items in the agreement, the conflict on delivery standards and dates, inflexible regulations, and lack of proper infrastructure and facilities. Ultimately, the study provides an outlook into the industry's future and provides field experts’ recommendations for better cooperation.